2008
DOI: 10.1007/s10725-007-9252-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sugars on auxin-mediated LeEXPA2 gene expression

Abstract: The paper deals with the effect of sugars on LeEXPA2 expression in tomato (Lycopersicon esculentum) hypocotyl segments, which is a wellstudied system for analysis of cell elongation. We tested the interactions between sugars and different plant hormones classically known to be involved in plant growth. We found the induction of LeEXPA2 transcript accumulation to be positively affected by the presence of sucrose and other metabolizable sugars. The effect mediated by sorbitol and by a non-metabolizable glucose a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 76 publications
(89 reference statements)
1
7
0
Order By: Relevance
“…Considering that we do not know how ACh could be taken up from the medium by the plant tissue, a concentration of 50 μM ACh was chosen for further experiments. From our previous work [ 42 ] we already know that if the segment elongation has to be monitored, the presence of sucrose is an essential requirement to sustain the auxin-induced LeEXPA2 transcript in a 16 h-long experiment. We are also aware that sucrose is more than an energy supply in the auxin induced expansin transcription [ 41 , 42 ], and we decided to take these observations into account in all the experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Considering that we do not know how ACh could be taken up from the medium by the plant tissue, a concentration of 50 μM ACh was chosen for further experiments. From our previous work [ 42 ] we already know that if the segment elongation has to be monitored, the presence of sucrose is an essential requirement to sustain the auxin-induced LeEXPA2 transcript in a 16 h-long experiment. We are also aware that sucrose is more than an energy supply in the auxin induced expansin transcription [ 41 , 42 ], and we decided to take these observations into account in all the experimental conditions.…”
Section: Resultsmentioning
confidence: 99%
“…They allow turgor-driven cell expansion by disrupting hydrogen bonds of the wall polysaccharides, and they are involved in a variety of physiological responses such as root growth [ 58 ], internode elongation [ 59 ], leaf development [ 60 ], fruit development [ 61 ], floral development [ 62 ], fruit maturation [ 63 , 64 ], and seed germination [ 65 ]. They are expressed in the apical meristem [ 66 ] and in active elongating tomato hypocotyl tissues [ 41 , 42 , 67 ]; they also play important roles during abiotic stress response [ 68 70 ]. Expansin activity is shown to be regulated by many factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are involved in many other processes and act also as metabolite signalling molecules that activate specific or hormone-crosstalk transduction pathways, resulting in important modifications of gene expression (Smeekens, 2000;Rolland et al, 2002;Gibson, 2005;Koch, 1996). Arru et al (2008) showed that sucrose at concentrations of range of 15 to 120 mM did not enhance the growth of tomato hypocotyls segments induced by 2,4-D or brassinolide, but sucrose at a concentration of 15 mM or higher in the presence of 2,4-D or brassinolide induced expansin gene LeEXPA2 transcript, member of a multigene family of extracellular proteins that mediate cell wall extension and relaxation during growth. Cui et al (2010) showed that high content of sucrose in adventitious root cultures of Hipericum perforatum resulted in osmotic stress and, in turn, induced the accumulation of secondary metabolites.…”
Section: Effect Of Soluble Sugars On Chlorophylls and Phenolic Compoumentioning
confidence: 99%
“…Once inside, hexoses have a great capacity to stimulate specific sugar sensors (Koch 2004 and references therein) and the resulting signals can alter expression of diverse genes (Smeekens 2000;Rolland et al 2002;Sherson et al 2003). With their hydrolytic activity, therefore, invertases are potentially strong effectors of widely varying developmental processes LeClere et al 2008), including the biosynthesis and perception of auxins and abscisic acid (Koch 2004 and references therein; Arru et al 2008). Hormone sensing by cultured cells is a prerequisite for cell growth, which has restricted in the past a wider application of plant cell cultures (Chang and Sim 1995).…”
Section: Introductionmentioning
confidence: 99%